HUBUNGAN USIA, JAM KERJA, JOB DEMAND, DAN JOB CONTROL DENGAN STRES KERJA PADA STAFF PT. ADHI KARYA (PERSERO) TBK. PROYEK PEMBANGUNAN HOTEL GRANDHIKA SEMARANG - Kusuma Handayani; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Job stress is the emotional state that arises because of the discrepancy between the level of demand with an individual's ability to cope with work stress he faced. Human resources or labor was instrumental in the company. The purpose of this study was to analyze the relationship between age, working hours, job demand and job control with job stress on the staff of PT. Adhi Karya (Persero) Tbk. Hotel Grandhika SemarangDevelopment Project. This type of research is a kind of analytic survey research with cross sectional study. The population of the research is the staff of PT. Adhi Karya (Persero) Tbk. Hotel Grandhika Semarang Development Project totaling 40 people. The sample in this study were drawn from the total population. Work stress was measured using the Live Event Scale. Statistical analysis using Rank Spearman correlation test. The results showed there is no correlation between age (sig = 0.846), job demand (sig = 0.425), and job control (sig = 0.475) with work stress. There is a correlation between working hours (sig = 0.037) with work stress. Companies should consider the overtime rules set by the government to avoid fatigue due to working hours are too long, holding regular exercise to maintain fitness, and assign tasks according to expertise of workers in order to reduce the risk of work stress.